Strengthening Laboratory Functions in Improving the Quality of Islamic Education Management Study Program IAIN Curup - Muhammad Amin; Rambat Nur Sasongko; Manap Somantri; Nirwana Nirwana; Arsil Arsil; Karliana Indrawari (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
The study program has many practical courses and wants to graduate to have real skills. The IAIN Curup Islamic Education Management study program directs its graduates to become educational staff at Islamic education institutions and agencies that handle education, become institutional managers, become Islamic education management researchers, and become planners and developers of ICT-based learning resources. So the existence or availability of a laboratory is a must. The research objectives were to determine the needs of lecturers and students of the IAIN Curup Islamic Education Management Study Program for laboratories and to determine the strengthening of laboratories in improving the quality of the IAIN Curup Islamic Education Management Study Program. This type of field research (Field Research) with qualitative research methods. Sources of data from the Head of Study Program, lecturers, laboratory managers and students of the MPI IAIN Curup study program, observation data collection techniques, interviews and documentation. Researchers analyzed the data with the stages of reducing data, presenting data, and drawing conclusions. The results of the research are the need for lecturers and students of the IAIN Curup Islamic Education Management Study Program to strengthen the function of labor because there is a mandatory leadership practice course for Islamic Education Management students, and students are required to have various abilities, both work skills, knowledge, and the ability to become leaders. Strengthening the labor function of the IAIN Curup Islamic Education Management Study Program is carried out in a number of stages, namely (1) creating a labor organization structure consisting of the Chair of the Labor, secretary, laboratory assistant, technicians and students, (2) making laboratory administration, (3) preparing laboratory facilities and infrastructure. study program, (3) create a labor curriculum. And (4) study program labor is designed with a U-shape model.